Self‐Assembly of Hexameric Macrocycles from PtII/Ferrocene Dimetallic Subunits – Synthesis, Characterization, Chemical Reactivity, and Oxidation Behavior (Eur. J. Inorg. Chem. 35/2015). Issue 35 (December 2015) - Giannetto, Antonino; Puntoriero, Fausto; Notti, Anna; Parisi, Melchiorre F.; Ielo, Ileana; Nastasi, Francesco; Bruno, Giuseppe; Campagna, Sebastiano; Lanza, Santo
Abstract : The cover picture shows two different representations of the structure of a hexameric species. The Pt II centers lie in two parallel planes, and the six ferrocene units are coplanar and directed to the center of the hexagon, which enables strong electronic interactions. The assembly can be assembled/disassembled at will, by addition of acids and/or bases. Details are discussed in the article by M. F. Parisi, S. Campagna, S. Lanza et al. onp. 5730 ff . For more on the story behind the cover research, see theCover Profile .